Laparoscopic Cholecystectomy: Some Advantages or Just an Artifice of New Technology?. Issue 4 (1991) - Penninckx, F.; Aerts, R.; Kerremans, R.; Koninckx, P. R.
Abstract : Twelve selected patients undergoing cholecystectomy were operated in a prospective randomised study by laparoscopy (CO2 laser) or by classic surgery. Our preliminary results suggest that laparoscopic cholecystectomy is of clinical benefit as compared to classic cholecystectomy since it reduces the surgical trauma, limiting weight loss and shortening the hospital stay.